Study on the physico-chemical characteristics of longan (Euphoria longana) germplasm (Bangladesh Journal of Agricultural Research, 2012)
A study on the physico-chemical characteristics of 15 promising longan germplasm was carried out at the fruit Research Farm of Horticulture Research Centre (HRC) as well as laboratory of Post harvest Technology Section of HRC and the Central Laboratory of Bangladesh Agricultural Research Institute, Joydebpur, Gazipur. The experiment was conducted during the fruiting season of 2010. Fifteen promising lines of longan germplasm including BARI Anshphal-1, BARI Anshphal-2, EL-Joy 003 to EL-Joy 015 of 12 years old were included in this experiment. A wide range of variations were observed among the germplasm in respect of different characteristics under the present study. Per cent edible portion was the highest in EL-Joy 010 (76.57 %), EL-Joy 006 (74.55%), EL-Joy 003 (74.20 %) and the lowest in EL-Joy 012 (65.10 %). Total reducing and non-reducing sugar was the maximum in EL-Joy 009 (6.94 %) and BARI Anshphal-2 (16.50 %), respectively. BARI Anshphal-1 contained the highest amount of ascorbic acid (13.00 mg/100 g) and EL-Joy 009 possessed the maximum total soluble solids (22.30 %). The study revealed that BARI Anshphal-1, BARI Anshphal-2, EL-Joy 003, EL-Joy 006, EL-Joy 009, EL-Joy 010 were the best in respect of physical and chemical characteristics of fruits. Bangladesh J. Agril. Res. 37(3): 441-447, September 2012 DOI: http://dx.doi.org/10.3329/bjar.v37i3.12087